Appraising LaQshya’s potential in measuring quality of care for mothers and newborns: a comprehensive review of India’s Labor Room Quality Improvement Initiative - Shalini Singh; Zabir Hasan; Deepika Sharma; Amarpreet Kaur; Deeksha Khurana; J N Shrivastava; Shivam Gupta (BMC Pregnancy and Childbirth, 2024)
Abstract Background Poor intrapartum care in India contributes to high maternal and newborn mortality. India’s Labor Room Quality Improvement Initiative (LaQshya) launched in 2017, aims to improve intrapartum care by minimizing complications, enforcing protocols, and promoting respectful maternity care (RMC). However, limited studies pose a challenge to fully examine its potential to assess quality of maternal and newborn care. This study aims to bridge this knowledge gap and reviews LaQshya’s ability to assess maternal and newborn care quality. Findings will guide modifications for enhancing LaQshya’s effectiveness. Methods We reviewed LaQshya’s ability to assess the quality of care through a two-step approach: a comprehensive descriptive analysis using document reviews to highlight program attributes, enablers, and challenges affecting LaQshya’s quality assessment capability, and a comparison of its measurement parameters with the 352 quality measures outlined in the WHO Standards for Maternal and Newborn Care. Comparing LaQshya with WHO standards offers insights into how its measurement criteria align with global standards for assessing maternity and newborn care quality. Results LaQshya utilizes several proven catalysts to enhance and measure quality- institutional structures, empirical measures, external validation, certification, and performance incentives for high-quality care. The program also embodies contemporary methods like quality circles, rapid improvement cycles, ongoing facility training, and plan-do-check, and act (PDCA) strategies for sustained quality enhancement. Key drivers of LaQshya’s assessment are- leadership, staff mentoring, digital infrastructure and stakeholder engagement from certified facilities. However, governance issues, understaffing, unclear directives, competency gaps, staff reluctance towards new quality improvement approaches inhibit the program, and its capacity to enhance quality of care. LaQshya addresses 76% of WHO’s 352 quality measures for maternal and newborn care but lacks comprehensive assessment of crucial elements: harmful labor practices, mistreatment of mothers or newborns, childbirth support, and effective clinical leadership and supervision. Conclusion LaQshya is a powerful model for evaluating quality of care, surpassing other global assessment tools. To achieve its maximum potential, we suggest strengthening district governance structures and offering tailored training programs for RMC and other new quality processes. Furthermore, expanding its quality measurement metrics to effectively assess provider accountability, patient outcomes, rights, staff supervision, and health facility leadership will increase its ability to assess quality improvements.